POSTPOSITIONS IN THE UZBEK LANGUAGE: STRUCTURE, FUNCTIONS, AND PATHS OF GRAMMATICALIZATION - Izbaeva Nodira (Modern American Journals, 2025)
Function words, including both prepositions and postpositions, though relatively few in number compared to content words, play a crucial role in the organization of utterances. This article examines the specific features of adpositional units in the Uzbek language, focusing on postpositions whose morphological structure is notably complex. The relevance of the study arises from the need for a systematic, comprehensive, and objective description of the composition and structure of the functional-grammatical field of Uzbek postpositions. It also addresses the necessity of identifying regular relationships among postpositional units within this field –their classifications, paradigmatic, syntagmatic, and semantic connections, as well as their functional properties –which together form the foundation of the functional-communicative grammar of Uzbek postpositions.
Keywords: Postpositions, structure, semantics, boundaries, expansion of the class of postpositions, grammaticalization, criteria.